Patients with Hepatitis C Infection and Normal Liver Function: A Neuropsychological and Neurophysiological Assessment of Cognitive Functions - Jefferson Abrantes; Daniel Simplicio Torres; Carlos Eduardo Brandão-Mello (International Journal of Hepatology)
Several studies have proposed a link between chronic hepatitis C virus (HCV) infection and the development of cognitive disorders. However, the inclusion of confounding factors in their samples significantly limits the interpretation of the results. Therefore, here, we aimed to compare the neurophysiological and cognitive performance between patients with HCV infection and a control group after excluding other factors that may cause cognitive impairment. This cross-sectional, group-control, observational study was performed from September 12, 2014, to October 20, 2017. HCV-infected patients and healthy individuals between 18 and 77 years were considered eligible. The exclusion criteria included well-established causes of cognitive impairment, such as depression and cirrhosis. The participants were submitted to neuropsychological testing to evaluate global cognitive function (minimental), sustained attention, divided attention, selective attention, working memory, psychomotor speed, and executive function and to a neurophysiological evaluation using quantitative electroencephalograms and P300 cognitive evoked potentials. Among the 309 patients considered eligible for the study, we excluded 259 patients who had one or more characteristics from the preestablished exclusion criteria, 18 who did not undergo neuropsychological and neurophysiological testing, and five who exhibited depression. The final sample consisted of 27 patients each in the HCV and control groups. The groups did not differ in age, schooling, and sex. The patients in the HCV group exhibited poorer performances in the cognitive areas involving attention (p=0.01), memory (p=0.02), and psychomotor velocity (p=0.04) apart from exhibiting prolonged latency in the P3b component (p=0.03) and Z score (p=0.02) of the P300 evoked cognitive potential. In this study performed with strict selection criteria, on conducting neuropsychological and neurophysiological evaluations, we detected the presence of cognitive impairment characterized by the involvement of attention, working memory, psychomotor processing speed, and memory in the HCV group.